Chinese revolution : comparative perspectives on transformation of non-western societies - Mohanty, Manoranjan, 1942- (Delhi : Ajanta Publications, 1992)
Papers originally presented at an international conference held in Hangzhou, China, in November 1987.
Includes bibliographical references.
Keywords: Revolutions -- Congresses; China -- Politics and government -- 1912-1949 -- Congresses; China -- Politics and government -- 1949- -- Congresses; China -- Social conditions -- 1912-1949 -- Congresses; China -- Social conditions -- 1949- -- Congresses